Negotiating the Use of Biodiversity in Marine Areas beyond National Jurisdiction - Blasiak, Robert; Pittman, Jeremy; Yagi, Nobuyuki; Sugino, Hiroaki (Frontiers in Marine Science, 2016)
A relatively small group of states is disproportionately active in marine areas beyond national jurisdiction (ABNJ), raising questions of equity, while a myriad of sectoral regulations and guidelines spread across multiple international bodies has led to uneven conservation and use of biological diversity and resources in these areas. Within this context, the UN General Assembly resolved in 2015 to begin negotiations on an international legally-binding instrument to conserve and protect biodiversity in ABNJ, with the negotiations framed by four issues: (1) marine genetic resources, including questions on the sharing of benefits; (2) measures such as area-based management tools, including marine protected areas; (3) environmental impact assessments; (4) capacity building and the transfer of marine technology. Yet our analysis demonstrates that least developed countries (LDCs) and small island developing states (SIDS) are significantly under-represented in regional and international meetings on such issues, while the authorship of academic literature on these topics is dominated to an unusual extent by Organization for Economic Cooperation and Development (OECD) member states (97%). Statistical analysis of delegation statements delivered during the first round of negotiations following the UN General Assembly resolution also illustrates that the interests of OECD member states differ substantially from LDCs and SIDS, suggesting that imbalanced representation has the potential to result in skewed negotiations. Moreover, the restriction on negotiating parties not to undermine the mandate of existing organizations limits their maneuverability, and may hamper progress towards achieving ambitious time-bound commitments to promote sustainable resource use and reduce inequality (e.g. under the Sustainable Development Goals and Aichi Targets). With ABNJ covering half the world’s surface, self-interested compliance with new regulations is the most promising pathway to conservation and sustainable use, yet remains unlikely unless states feel their views, concerns and best interests have been reflected in the negotiated agreement.